Tracking the effect of roasting and fermentation on the metabolites of licorice root (Glycyrrhiza glabra L.) using UPLC-MS analysis combined with multivariate statistical analysis - Sarah S. Takla; Eman Shawky; Yasmin A. Mahgoub; Reham S. Darwish (BMC, 2023)
Abstract Background Roasting, honey-roasting and fermentation are the most common pre-processing procedures of licorice roots. They were shown to noticeably change the composition of extracts. In this work, the common alterations in licorice secondary metabolites by processing were interpreted. Comprehensive metabolic profiling of different studied samples was undergone. Methods UPLC-QqQ-MS/MS analysis coupled to various chemometric analysis models was implemented to unravel the effect of different pre-processing procedures on the chemical profile of licorice samples. Results UPLC-QqQ-MS/MS analysis designated 133 chromatographic peaks with saponins, flavonoids, chalcones and pterocarpans being the most abundant groups. Triterpene saponins dominated the secondary metabolites in the aqueous extracts, with fermented samples showing the highest relative amounts. Meanwhile the ethanol extracts showed significant amounts of chalcones. Melanoidins were only detected in roasted and honey roasted samples. Multivariate models indicated that roasting of samples induced a greater effect on the polar metabolites rather than nonpolar ones. Variable of importance (VIP) plot indicated that glycyrrhizin and its hydrolysis product glycyrrhetinic acid, trihdroxychalcone diglycoside, glabrone and glabridin are the main chemical features responsible for the discrimination of samples. Conclusion Coupling UPLC-MS/MS to multivariate analysis was a successful tool that unveiled the significant effect of different pre-processing methods on the chemical profile of processed and unprocessed licorice samples. Moreover, such coupling unraveled the discriminatory chemical compounds among tested samples that can be employed as markers for the processing procedure of licorice.